Integration of Multicultural Values ​​in the Development of Islamic Religious Education Curriculum - Rasyid, Musyrifah; Hidayat, Muhammad Ilham; Nurannisa, Ismi; Tang, Muhammad; Syahrul, M. (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Multiculturalism is an unavoidable social reality in human life. The diversity of religion, ethnicity, language, and culture is an inevitable reality that should serve as a source of strength rather than conflict. However, the lack of multicultural awareness often leads to social tensions. In this context, education plays a strategic role in instilling human values, tolerance, and respect for differences through an inclusive and multicultural-oriented curriculum, including in Islamic Religious Education (PAI). This study aims to analyze multicultural values, identify strategies for developing a multicultural-based curriculum, and examine the challenges and solutions in its implementation. The method used is a qualitative approach with a library research design, focusing on the exploration and analysis of various written sources such as books, scientific journals, articles, and relevant online materials. The results of the study indicate that the application of values such as tolerance, unity, mutual cooperation, and solidarity plays an important role in shaping inclusive student character. The strategies used include adjusting the educational philosophy toward a more humanistic approach, integrating cultural values into learning materials, implementing collaborative learning, and using comprehensive evaluation methods. In the context of Islamic Religious Education, the multicultural approach is effective in fostering religious moderation and tolerance, although it still faces obstacles such as limited resources and insufficient teacher training. Therefore, collaboration among the government, educational institutions, and society is needed to strengthen the implementation of multicultural curricula in schools.